A controlled clinical trial of a brief psycho-educational intervention for anxiety among in-school adolescents in Nigeria. Issue 1 (2nd January 2022) - Jibunoh, Olayinka; Ani, Cornelius
Abstract: This study evaluated if psycho-education can significantly reduce anxiety symptoms among Nigerian adolescents. Forty adolescents with highest ranked scores on the Spence Children's Anxiety Scale (SCAS) were selected from two schools (20 each from intervention and control schools). The intervention group received three sessions of group-based psycho-education about anxiety and relaxation techniques. Participants were aged 13–16 years and consisted of 12 male and 28 female pairs. Controlling for baseline SCAS scores, the psycho-educational intervention was not effective in reducing anxiety F (1, 36) = 1.56, p = 0.22. The lack of efficacy may be due to participants' very high baseline anxiety scores.